Bound and trailing vortices in the linearised theory of supersonic flow, and the downwash in the wake of a delta wing - Robinson, A.; Hunter-Tod, J. H. (College of Aeronautics, Cranfield, 1947)
The field of flow round a flat aerofoil at incidence can/may be regarded in linearised theory as the result of both bound and trailing vortices for supersonic as well as for low speed flight. This leads to a convenient method, given the lift distribution over an aerofoil, for calculating the flow round it at supersonic speeds. As an application of the results the downwash is calculated in the wake of a delta wing lying within the Mach cone emanating from its apex. The downwash is found to be least just aft the trailing edge and is everywhere less that the downflow at the aerofoil. It increases steadily to a limiting value which is attained virtually within two chord lengths of the trailing edge. The ratio of the downwash at any point in the wake to the downflow at the aerofoil decreases with increasing Mach number and apex angle.